Non-beany flavor soymilk fermented by lactic acid bacteria: Characterization, stability, antioxidant capacity and in vitro digestion - Chunyan Huo; Xiaoyu Yang; Liang Li (Food Chemistry: X, 2023)
LAB fermentation could reduce the beany flavor, the sensitization of soymilk and improve the digestibility of soymilk, easy to be accepted by consumers. This study evaluated the characterization, stability, in vitro digestion and antioxidant capacity of soymilk fermented by different Lactic acid bacteria (LAB). The results showed that fat content of L.plantarum-S (0.77 g/100 mL) was the lowest, which proved that L.plantarum had a significant effect on lipid degradation, the protein content of L.delbrueckii-S (23.01 mg/mL) was higher. L.delbrueckii-S and L.paracasei-S were more acceptable to people, as well as high overall ratings. L.paracasei fermented soymilk has better suspension stability and smaller particle size. The fermented soymilk showed higher free amino acids (FAA) content, peptide content and stronger antioxidant activity than soymilk after digestion. The soymilk fermented by L. plantarum contained higher FAA content and L.delbrueckii contained the highest peptide content compared with other strains. L.acidophilus-S and L.rhamnosus-S showed stronger DPPH scavenging rate and FARP, which were 57.03 % and 52.78 % stronger than unfermented soymilk, respectively. These results may be provided a theoretical basis for the strain screening of fermented soymilk.